And so it is... : a memoir of acceptance and hope - Sigler, Jamie-Lynn, 1981- (Harper, 2026)
"Jamie Lynn Sigler is both the girl-next-door and a superstar. Tapped at the young age of sixteen to star as Meadow Soprano, daughter of mob boss Tony Soprano, by the time the series ended in 2007, Jamie, then twenty-five, suffered from an eating disorder, kept private her diagnosis of MS, and entered a disastrous early marriage--all under the scrutiny of a less-than-kind public eye. Over the next years, Jamie would remarry, become a mother, launch a hugely popular podcast and, most recently, nearly lose her beloved son to a mysterious illness. Amidst the stardust showered and all the slings and arrows that life has thrown, Sigler emerges with grace and a generosity of spirit that she is ready to share. In this moving and fiercely honest memoir, she reflects on her life and her years on The Sopranos.But this is no tale of woe; Jamie guides us through her darkest moments and comes out the other side emboldened and not embittered. A natural storyteller, she shares memories of her time portraying Meadow Soprano and beyond, including her often painful journey of self-discovery. In this unflinching account, Jamie holds nothing back; her resilience, candor, and her heart-bursting capacity for love shine through on every page."--Provided by publisher.